2021
DOI: 10.1021/acsami.1c10698
|View full text |Cite
|
Sign up to set email alerts
|

Harvesting Hot Holes in Plasmon-Coupled Ultrathin Photoanodes for High-Performance Photoelectrochemical Water Splitting

Abstract: The harvesting of hot carriers produced by plasmon decay to generate electricity or drive a chemical reaction enables the reduction of the thermalization losses associated with supra-band gap photons in semiconductor photoelectrochemical (PEC) cells. Through the broadband harvesting of light, hot-carrier PEC devices also produce a sensitizing effect in heterojunctions with wide-band gap metal oxide semiconductors possessing good photostability and catalytic activity but poor absorption of visible wavelength ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 66 publications
(113 reference statements)
2
19
0
Order By: Relevance
“…For instance, Vahidzadeh et al reported that AuNPs embedded in a thin film of amorphous TiO 2 can inject hole holes in TiO 2 film which promotes PEC water oxidation. 392 Decoration of plasmonic nanoparticles on TiO 2 can not only improve the photocatalytic performance but can also control the product selectivity under different light irradiation. Zeng et al found that periodically modulated TiO 2 nanotubes (PMTiNTs) photonic crystal modified with AuNPs demonstrates CH 4 as the main product under solar simulated light while formaldehyde was a dominating product when the catalyst was irradiated with solar simulated/and or UV and 550 nm light.…”
Section: Photoactive Sacs For Ch 4 Ormentioning
confidence: 99%
“…For instance, Vahidzadeh et al reported that AuNPs embedded in a thin film of amorphous TiO 2 can inject hole holes in TiO 2 film which promotes PEC water oxidation. 392 Decoration of plasmonic nanoparticles on TiO 2 can not only improve the photocatalytic performance but can also control the product selectivity under different light irradiation. Zeng et al found that periodically modulated TiO 2 nanotubes (PMTiNTs) photonic crystal modified with AuNPs demonstrates CH 4 as the main product under solar simulated light while formaldehyde was a dominating product when the catalyst was irradiated with solar simulated/and or UV and 550 nm light.…”
Section: Photoactive Sacs For Ch 4 Ormentioning
confidence: 99%
“…[10] Nevertheless, if metal NPs are in intimate contact with an adjacent semiconductor, the excited carrier can be injected into semiconductor before the relaxation. [11][12][13] Plasmonic energy conversion from photoexcited metal NPs is a promising alternative path compared to conventional electron-hole separation in semiconductor materials. [14] Plasmon driven hot charge carrier transfer to semiconductors (SC) has been discussed in several excellent reviews.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from this scattering process, LSPR can be damped in several ways such as inter band damping, intra‐band (Landau), electron‐surface scattering and chemical interface damping mechanism (CID) [10] . Nevertheless, if metal NPs are in intimate contact with an adjacent semiconductor, the excited carrier can be injected into semiconductor before the relaxation [11–13] . Plasmonic energy conversion from photo‐excited metal NPs is a promising alternative path compared to conventional electron‐hole separation in semiconductor materials [14] .…”
Section: Introductionmentioning
confidence: 99%
“…The harvesting of hot holes in such plasmon-semiconductor heterojunctions is relatively rare [33][34][35] in comparison to the large number of reports on successful hot electron harvesting in junctions between n-type semiconductors and coinage metals. One major engineering problem is the difficulty in achieving high performance Schottky barriers between p-type semiconductors and high work function coinage metals.…”
Section: Introductionmentioning
confidence: 99%